Enuresis improvement and its associated factors among children attending enuresis clinic at Rusaifah - Hanan Mosad Al Matrafi, (Universiti Kebangsaan Malaysia, 2015)
Background: Enuresis is a common non-lethal health problem, causing a great deal of stress, confusion, and frustration to the suffering children, parents, and physicians. Objectives: Finding and evaluating the scope of improvement and factors associated with it among children attending enuresis clinic at Rusaifah Family Medicine Postgraduate Training Center in Makkah Al-Mukarramah. Subjects and Methods: The study was conducted at Rusaifah Family Medicine Postgraduate Training Center in Makkah Al-Mukarramah (June–August 2013). The targeted population was 600 patients with enuresis registered with the enuresis clinic at Al-Rusaifah Family Medicine Postgraduate Training Center. The sample size was calculated to be 150 using Epi Info, version 6. Medical records of patients with enuresis and a checklist designed by the researcher were used to obtain data covering all variables studied. Medical records were reviewed and the required information was pooled to a checklist designed to record data required for variables. Results: The response rate was 100%. A zero wetting per week improvement was found among 149 (99.3%), 54 (36%), and 9 (6%) in the first month, first 2 months, and first 3 months, respectively. The mean age of children with improved enuresis was found to be 9.38 years in the first month, 9.09 years in the first 2 months, and 11.33 years in the first 3 months, respectively, compared to that of those with non-improved enuresis (5 years, 9.51 years, and 9.23 years in the first month, first 2 months, and first 3 months). This difference was not significant except in the first 3 months (p < 0 .04). Other studied variables (age at toilet training, gender, nationality, spontaneous wakening for toilet, fear of toilet, easy access to toilet, hospitalization, parental separation, delayed milestones, fluid restriction, school/home conflict, urinary tract infection symptoms, punishment, and rewards) were not significantly associated with the degree of improvement for enuresis. Conclusion: The degree of improvement (zero wetting per week) was high in the first month then and then declined steadily in the first 2 months and in the first 3 months.